Environmental History sebagai Perspektif Historiografi dalam Kajian Sejarah Peradaban Islam - A Ainul Yaqin; Ahmad Efendi Yusuf (Kartika: Jurnal Studi Keislaman, 2026)
The development of modern historiography has broadened historical inquiry through interdisciplinary perspectives, one of which is Environmental History, which positions the environment as an integral element in understanding the dynamics of human civilization. Nevertheless, the study of Islamic Civilization History in Indonesia continues to be dominated by political, dynastic, biographical, educational, and cultural approaches, while the use of Environmental History as a historiographical perspective remains limited. This article aims to examine the relevance of Environmental History and propose it as an alternative perspective for enriching the study of Islamic Civilization History. This study employs a library research method using a conceptual-historiographical approach. Data were collected from scholarly literature, including books and articles published in reputable academic journals, and analyzed using content analysis to identify and interpret key concepts. The findings demonstrate that Environmental History offers a more comprehensive historiographical framework by emphasizing the interaction between humans, the environment, and ecological change in shaping Islamic civilization. This perspective complements existing historiographical approaches while opening new directions for broader and more multidimensional research on Islamic Civilization History.